THE CONCEPT OF THE NATIONAL HERO «QUONAKH» IN PAINTING AND GRAPHICS DURING THE CHECHEN CRISIS (90S OF THE TWENTIETH CENTURY) - Zarema R. Khamzatova (Russian Studies in Culture and Society, 2023)
The paper is devoted to the research and study of the artistic interpretation of the concept of “Quonakh” (national hero) in Chechen painting and graphics in the 1990s.